A Review of CXCL1 in Cardiac Fibrosis - Wu, Cheng-Long; Yin, Ran; Wang, Su-Nan; Ying, Ru (Frontiers in Cardiovascular Medicine, 2021)
Chemokine C-X-C motif ligand-1 (CXCL1), principally expressed in neutrophils, macrophages and epithelial cells, is a valid pro-inflammatory factor which performs an important role in mediating the infiltration of neutrophils and monocytes/macrophages. Elevated serum level of CXCL1 is considered a pro-inflammatory reaction by the organism. CXCL1 is also related to diverse organs fibrosis according to relevant studies. A growing body of evidence suggests that CXCL1 promotes the process of cardiac remodeling and fibrosis. Here, we review structure and physiological functions of CXCL1 and recent progress on the effects and mechanisms of CXCL1 in cardiac fibrosis. In addition, we explore the role of CXCL1 in the fibrosis of other organs. Besides, we probe the possibility that CXCL1 can be a therapeutic target for the treatment of cardiac fibrosis in cardiovascular diseases.